A new species of Deiregyne (Orchidaceae, Spiranthinae) from Mexico - Soto, Miguel Á.; Salazar, Gerardo A. (Instituto de Ecología, A.C., 2022)
Deiregyne tenorioi Soto Arenas & Salazar, a new orchid species from the Mexican states of Hidalgo, Estado de México, Oaxaca, Puebla, and Tlaxcala, is described and illustrated. It is similar to D. eriophora (B.L. Rob. & Greenm.) Garay and D. chartacea (L.O. Williams) Garay, differing from the former in the sparsely glandular-pubescent inflorescence rachis and ovary (vs. lanuginose), odorless flowers and proportionately longer, narrower labellum with bright green to lemon yellow, narrow throat with straight sides (vs. golden yellow, wide throat with rounded sides); from the latter it differs in larger flowers with sepals and petals not tinged with greenish-brown below the middle, spreading lateral sepals (vs. strongly recurved), and proportionately longer, narrower distal labellum lobe.